The Role of Iraqi Online Journalism in Covering Security Events: An Analytical Study of Iraqi News Websites - Rasha Saheb Hadi, Asst. Lecturer (lark, 2026)
Over the past two decades, Iraq has witnessed rapid security and political transformations, placing security events at the forefront of public attention. Electronic journalism has emerged as a primary tool relied upon by citizens to follow these events, thanks to its speed and continuous updates. The research problem lies in the noticeable disparity among Iraqi news websites in their approaches to covering security events, and the extent to which they adhere to professional standards and balance journalistic scoops with social responsibility. The study also derives its importance from the growing role of digital media in shaping the social and political awareness of the Iraqi public regarding security issues. Scientifically, it contributes to filling a research gap related to analyzing the professional performance of news websites. Socially, it helps to rationalize security coverage in a way that promotes social peace and reduces sensationalism and rumors. The study aims to reveal the role of Iraqi electronic journalism in covering security events and to understand the strategies of electronic media in addressing news related to conflicts, bombings, armed attacks, and other security developments. The study adopted a descriptive-analytical approach using content analysis. Data was collected from a purposive sample of Iraqi online news sites, including Alsumaria News, Al Sharqiya News, Noon News, and Rudaw. The analysis covered security-related news published during a specific time period and focused on the following categories: type of source, writing style, media framing, and the degree of balance and objectivity in coverage. The research population consisted of Iraqi online news sites. A purposive sample was selected from the most prominent and influential sites among the Iraqi public during the study period..